2009
DOI: 10.1021/la900501n
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Characterization of Individualized β-Lactoglobulin Microgels Formed upon Heat Treatment under Narrow pH Range Conditions

Abstract: Aqueous dispersions of demineralized beta-lactoglobulin (beta-lg) were held at 85 degrees C for 15 min at a constant protein concentration of 1 wt % in the pH range of 3.0-7.0. This led to denatured protein content ranging from 20% (pH 3.0) to 90% (pH 5.0). The protein aggregates formed were characterized as to their stability to sedimentation (turbidity), morphology, size, surface charge, ANS surface hydrophobicity, and content in accessible thiol groups. Additionally, the changes in secondary structures of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(84 citation statements)
references
References 71 publications
11
71
1
Order By: Relevance
“…The turbidity of a mixed biopolymer system is often a consequence of phase separation resulting in the formation of particles that scatter light (Schmitt et al 2009). Turbidity measurements on gelatin-gum GFS can provide information about electrostatic complex formation between the two biopolymers.…”
Section: Effect Of Gums On the Turbidity Of Gelatin-gum Gfsmentioning
confidence: 99%
“…The turbidity of a mixed biopolymer system is often a consequence of phase separation resulting in the formation of particles that scatter light (Schmitt et al 2009). Turbidity measurements on gelatin-gum GFS can provide information about electrostatic complex formation between the two biopolymers.…”
Section: Effect Of Gums On the Turbidity Of Gelatin-gum Gfsmentioning
confidence: 99%
“…There is a recognition that β-lg could form fibrils when heated at low pH and low ionic strength; β-lg gels with a fine-stranded microstructure can be made at pH < 4 . It is reported that far below proteins' pI (and also above), aggregates of pure β-lg solutions at 1 % are characterized by a worm-or fibrillar-like structure, instead of a spherical one (Mezzenga and Fischer 2013;Schmitt et al 2009). Several techniques have been reviewed for the production β-lg or WPI fibrils (Loveday et al 2012).…”
Section: Temmentioning
confidence: 99%
“…This interest arises with the possibility of designing whey protein hydrogels' size from micrometers to nanometers, thus allowing their incorporation in foods to impart desirable textural properties. These structures may also be used to protect and improve delivery of value-added bioactive compounds through microencapsulation and nano-encapsulation techniques (Augustin 2003;Bhopatkar et al 2012;Chen and Subirade 2007;Chen et al 2006;Gunasekaran et al 2007;Livney 2010;Nicolai et al 2011;Schmitt et al 2009). However, the mechanism of protein unfolding, aggregation, and gelation is rather complex.…”
Section: Introductionmentioning
confidence: 99%
“…The process of denaturation of globular whey proteins is assumed to consist of at least two steps: a partial unfolding of the native protein, and a subsequent aggregation of unfolded molecules (Nielsen, Singh, & Latham, 1996). In particular, unfolding of the native conformation of globular whey proteins at neutral pH leads to exposure of free sulfhydryl groups (SH) and hydrophobic amino acid side-chains, normally occluded within bovine serum albumin (BSA) and lg (Kazmierski & Corredig, 2003;Schmitt et al, 2009;Shimada & Cheftel, 1989). With further heat treatment, free SH may rapidly interchange with existing disulfide bonds to generate new inter-and intramolecular disulfide bonds that will engage toward protein aggregation (Fairley, Monahan, German, & Krochta, 1996;Schokker, Singh, Pinder, & Creamer, 2000).…”
Section: Introductionmentioning
confidence: 99%